Analysis of Influence of Tool Installation Error on the Tooth Profile Surface of Face Gear - Li Xiaozhen; Sheng Dongping; Zhang Donglin (Jixie chuandong)
In order to analyze the influence of the tool installation error on the tooth profile surface of the face gear,the meshing coordinate system of the face gear machining with the tool installation error is established. The tooth profile surface equation of face gear is derived by using the enveloping principle. The model of the tooth profile surface with the tool offset and the crossed axes angle error is built by using the numerical simulation method,the influence of tool offset and crossed axes angle error on the face gear tooth profile surface is analyzed. The research result shows that the profile surface of the face gear is not sensitive to the installation error of the tool.